Kidney - Dunea, George; Arruda, Jose A. L.; SpringerLink (Online service) (New York : Springer New York : Imprint: .)
Kidney was ceased at the end of the year 2010. Kidney was an international journal that offered readers a review of current literature focusing on nephrology.
Keywords: Nephrology; Urology; Nephrology; Urology